High expression of uracil DNA glycosylase determines C to T substitution in human pluripotent stem cells - Ju-Chan Park; Hyeon-Ki Jang; Jumee Kim; Jun Hee Han; Youngri Jung; Keuntae Kim; Sangsu Bae; Hyuk-Jin Cha (Elsevier, 2022)
Precise genome editing of human pluripotent stem cells (hPSCs) is crucial not only for basic science but also for biomedical applications such as ex vivo stem cell therapy and genetic disease modeling. However, hPSCs have unique cellular properties compared to somatic cells. For instance, hPSCs are extremely susceptible to DNA damage, and therefore Cas9-mediated DNA double-strand breaks (DSB) induce p53-dependent cell death, resulting in low Cas9 editing efficiency. Unlike Cas9 nucleases, base editors including cytosine base editor (CBE) and adenine base editor (ABE) can efficiently substitute single nucleotides without generating DSBs at target sites. Here, we found that the editing efficiency of CBE was significantly lower than that of ABE in human embryonic stem cells (hESCs), which are associated with high expression of DNA glycosylases, the key component of the base excision repair pathway. Sequential depletion of DNA glycosylases revealed that high expression of uracil DNA glycosylase (UNG) not only resulted in low editing efficiency but also affected CBE product purity (i.e., C to T) in hESCs. Therefore, additional suppression of UNG via transient knockdown would also improve C to T base substitutions in hESCs. These data suggest that the unique cellular characteristics of hPSCs could determine the efficiency of precise genome editing.